Analisis Pengaruh Daya Tarik Iklan, Influencer Marketing dan Online Customer Reviews Terhadap Keputusan Pembelian Elektronik Tokopedia - Ahmad Farhat; Soelaeman Rasyid (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the influence of advertising appeal, influencer marketing, and online customer reviews on purchasing decisions in Tokopedia’s e-commerce platform. The research applied a quantitative method using survey questionnaires distributed to 109 Tokopedia users in Jakarta. Data were analyzed using path analysis with SmartPLS. The results indicate that advertising appeal and influencer marketing significantly and positively affect purchasing decisions, while online customer reviews show no significant impact. These findings suggest that Tokopedia consumers, particularly in electronic products, are more influenced by attractive advertising and influencer endorsements than by online reviews. The study is limited by its sample size, geographic scope, and product focus on electronics. Future research is recommended to expand respondents and product categories for broader insights.